The Influence of Brand Image, Online Customer Reviews, and Price on Wardah Skincare Purchase Decisions Among Students of the Management Study Program Warmadewa University - Wulandari, Ni Kadek Alesya; Sariani, Ni Ketut; Pertama, I Gde Agung Wira (PT Keberlanjutan Strategis Indonesia, 2026)
Contemporary consumers are more selective when purchasing goods and services. For this to be successful, businesses need to understand what customers want and provide it to them. Price, online customer reviews, and how the brand is perceived all influence purchases. This study examines how price, online customer reviews, and brand image influence purchase choices. The sample consisted of 89 economics students from Warmadewa University who used Wardah skincare products. SPSS version 26 was used for the quantitative study. Several tests were used to analyze the data, including validity, reliability, classical assumption tests, multiple linear regression, F-tests, and t-tests. The study found that consumers were positively and significantly influenced by price, online customer reviews, and brand image when making purchasing decisions. People are highly influenced by price, online customer reviews, and brand image when making purchases. Scientists recommend that Wardah Skincare improve the quality of its products by developing new ideas and using better ingredients. Improve the quality of raw materials, blending, and dosage. Products must meet consumer expectations, and prices must reflect product benefits.